Factual/Fictional Eye-Witnessing of the Political Transition in South Africa – Mike Nicol’s The Waiting Country: A South African Witness - Bartnik, Ryszard (Department of Dutch and South African Studies, Faculty of English, 2012)
This paper concerns Mike Nicol’s memoir The Waiting Country, in which the author positions himself as an eyewitness of dramatic and outstanding events going on in South Africa before and during the elections of 1994. The primary goal the author assumes is to interpret the time of the political transition, hence his insistence on the legitimization of storytelling. In the text one finds, as explained by Nicol “[s]tories [he] ha[s] taken in and made part of what it is to live here. Stories [he] use[s] to depict [...] what is happening and what [he] think[s] is happening” (Nicol 1995: 12). Through a mosaic of cross-racial and literary viewpoints his text takes on the guise of a sincere and serious attempt at understanding the troubled South African self, both in its individual and collective dimension, and explaining that self to others. Nicol’s factual/fictional version of the country’s historical moment depicts the mixed feelings of exhilaration and anxiety everyone seems to have felt on the threshold of this fundamental, systemic change.
Keywords: post-apartheid South Africa; democratic elections; memoir; referential writing; the past vs. the future; factual and fictional writing